PAI Teacher’s Creativity In Improving The Theaching Quality of PAI Material In MTsN 1 Ponorogo - Heru Saiful Anwar; Muhammad Anggi Hidayat (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Religioous education is one of the most important education in human life, specifically about the teachings of islam. Thus, islamic religious education material not only becomes knowledge, but also can shape the attitudes and personality of students. So that they become faithful and devoted human beings. In general, the quality of islamic religious education has not met expectations. Because there are several indications such as the ability to read the Qur’an and the ability to worship are still lacking. To overcome this problem, teachers must be able to improve the quality of islamic religious learning in schools. So that it will have an impact on improving the quality of islamic religious education in Indonesia. One of them is having creativity in teaching and learning programs. Namely by creating a new and more interesting atmosphere in every learning activity at school. Like the one in the state MTsN 1 Ponorogo. The purpose of this study was to find out the creativity of Pai’s teacher in using methods, media, and learning resources in the state Mts 1 Ponorogo. The result of this study are Pai’s creativity in using methods, namely by applying varied and appropriate methods in learning. And Pai’s teacher also develops the media besides those prepard by the school. And in addition, Pai’s Teacher also uses learning resources in the classroom and outside the classroom, even outside the school to improve the quality of learning in PAI Material.